6Li+28Si reaction cross sections at sub-barrier energies - Pakou, A.; Musumarra, A.; Pierroutsakou, D.; Alamanos, N.; Assimakopoulos, P. A.; Divis, N.; Doukelis, G.; Harissopulos, S.; Kalyva, G.; Lagoyannis, A.; Mertzimekis, T. J.; Nicolis, N. G.; et al. (HNPS Advances in Nuclear Physics, 2019)
Total reaction cross sections at near barrier energies (9-13 MeV) were measured for the system 6Li+28Si adopting a new technique. The results will be discussed in terms of the threshold anomaly at barrier